2020
DOI: 10.21203/rs.3.rs-79619/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing COVID-19 related anxiety among nurses in Malawi

Abstract: Introduction: Psychological wellbeing of nurses is crucial for them to effectively discharge their duties. However, COVID-19 related anxiety can interfere with nurses’ performance in their duties and reduce their self-efficacy levels.Aim: This study aimed at assessing COVID-19 related anxiety among nurses in Malawi.Method: This was a cross-sectional study that collected data from 102 nurses online. Data were analysed using descriptive statistics and receiver operating curve analysis.Results: This study found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
8
2
Order By: Relevance
“…Further, increased social support and higher personal resilience among hospital nurses may have contributed to lower levels of coronavirus anxiety when compared to public health nurses. Overall, the percentage of nurses reporting coronaphobia in the current study was higher when compared to previous studies where dysfunctional anxiety related to COVID-19 ranged from 3.3% to 46.3% (Chorwe-Sungani 2020; Saricam, 2020; Labrague & De los Santos, 2020a).…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Further, increased social support and higher personal resilience among hospital nurses may have contributed to lower levels of coronavirus anxiety when compared to public health nurses. Overall, the percentage of nurses reporting coronaphobia in the current study was higher when compared to previous studies where dysfunctional anxiety related to COVID-19 ranged from 3.3% to 46.3% (Chorwe-Sungani 2020; Saricam, 2020; Labrague & De los Santos, 2020a).…”
Section: Discussioncontrasting
confidence: 84%
“…Mounting evidence has shown that approximately 22% to 37% of HCWs suffered from abnormal levels of anxiety due to the virus (Gupta et al ., 2020; Pappa et al . 2020), and among this group of HWCs, nurses reported the highest incidence, which ranged from 25.5% to 92% (Chorwe-Sungani 2020; Saricam, 2020; Labrague & De los Santos, 2020a). Female nurses (Bitan et al ., 2020; Pappa et al ., 2020), and those who were assigned in COVID-19 designated institutions, were twice as anxious as those nurses who worked in non-coronavirus specific hospitals (Mora-Magana et al ., 2020; Pouralizadeh et al ., 2020).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…All studies were conducted between January 2020 and September 2020: eight in January, 36 in February, 13 in March, 13 in April, six in May, two in June, two in July and one in September. Twenty preprint studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ] were included in the analyses. All studies included in this meta-analysis were of cross sectional design.…”
Section: Resultsmentioning
confidence: 99%
“…The overall pooled point estimates of prevalence for anxiety varied between 8% and 91%, which was reported by 73 studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [28] , [29] , [30] , 32 , 34 , 35 , [37] , [38] , [39] , [42] , [43] , [44] , [45] , [46] , 48 , 49 , 51 , [53] , [54] , [55] , [56] , [57] , 62 , [64] , [65] , [66] , [67] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] ,…”
Section: Resultsmentioning
confidence: 99%